Canker disease of willow and poplar caused by Cryptosphaeria pullmanensis recorded in China. Issue 4 (9th March 2016) - Ma, R.; Zhu, Y.‐F.; Fan, X.‐L.; Tian, C.‐M.
Summary: A new canker disease of Salix alba and Populus alba has been observed in Xinjiang, China. Black circular spots on dead branches and stems are the symptoms of the disease. Sixty‐seven isolates recovered from Salix matsudana, S. alba and Populus alba were identified as Cryptosphaeria pullmanensis based on morphological features and multigene phylogeny. Pathogenicity tests were performed on S. alba and P. alba stems using the C. pullmanensis isolates. Cankers on and Cryptosphaeria pullmanensis of C. pullmanensis from the stems fulfilled Koch's postulates and confirmed C. pullmanensis as the causal agent of the canker disease. C. pullmanensis is characterized by its yellow stromatic tissue surrounded by a black conceptacle with regularly arranged multiple locules sharing common walls and hyaline, allantoid, aseptate conidia (mean size 7.42 × 1.72 μ m). This is the first report of C. pullmanensis causing Cryptosphaeria canker in China, and S. alba and P. alba are new host records for C. pullmanensis .